2007
DOI: 10.1590/s0100-40422007000800036
|View full text |Cite
|
Sign up to set email alerts
|

Indução assimétrica 1,5-Anti na adição de enolatos de boro de metilcetonas beta-oxigenadas a aldeídos

Abstract: # Esta revisão é dedicada à Prof a . Helena M. C. Ferraz em reconhecimento a sua grande contribuição acadêmica e científica para a área de Química Orgânica no Brasil. High levels of substrate-based 1,5-stereoinduction are obtained in the boron-mediated aldol reactions of β-oxygenated methyl ketones with achiral and chiral aldehydes. Remote induction from the boron enolates gives the 1,5-anti adducts, with the enolate π-facial selectivity critically dependent upon the nature of the β-alkoxy protecting group. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
1
2
0
1
Order By: Relevance
“…Thus, it is clear that the major contribution to the sense of 1,5- syn induction observed in aldol reactions involving boron enolates of methylketones 1 − 4 is due to the volume of the substituent at the β-position and not to electronic effects, as stated previously …”
supporting
confidence: 53%
See 1 more Smart Citation
“…Thus, it is clear that the major contribution to the sense of 1,5- syn induction observed in aldol reactions involving boron enolates of methylketones 1 − 4 is due to the volume of the substituent at the β-position and not to electronic effects, as stated previously …”
supporting
confidence: 53%
“…Since then, numerous approaches from the research groups of Paterson, Evans, Denmark, Dias, and others have shown that the sense of induction in aldol reactions of boron enolates of β-alkoxy methylketones with aldehydes favors the formation of the 1,5- anti diastereoisomer. However, we demonstrated that it is possible to obtain good levels of 1,5- syn induction from β-trifluoromethyl and β-trichloromethyl-β-alkoxy methylketones independent of the nature of the β-alkoxy protecting group (Scheme ). , …”
mentioning
confidence: 99%
“…Furthermore, in the asymmetric version of the reaction, new stereogenic carbons can be generated with high levels of selectivity. [4][5][6][7][8] In biological systems, aldol reactions are promoted reversibly and stereoselectively by a group of enzymes known as fructose 1,6bisphosphate aldolases, or simply aldolases. 1,4,[9][10][11] Since its first use in 1971, [12][13][14] the amino acid L-proline has showed itself as an efficient and versatile organocatalyst for aldol reactions.…”
Section: Introductionmentioning
confidence: 99%
“…39 Para o entendimento de reações aldólicas de metilcetonas, onde um único centro estereogênico é formado, assim como para compreensão dos fatores envolvidos na estereoindução 1,5 de metilcetonas, recomendam-se os trabalhos de Dias e colaboradores. 40 Aldolatos podem equilibrar suas formas sin e anti por enolização ou por aldolização reversa. Entretanto, na maioria dos casos, o mecanismo para o equilíbrio sin-anti parece envolver a aldolização reversa.…”
Section: Figura 2 Nomenclatura Para Configuração Relativa Proposta Punclassified